Mechanical, Cellular, and Proteomic Properties of Laryngotracheal Cartilage. (July 2019) - Pauken, Christine M.; Heyes, Richard; Lott, David G.
The larynx sometimes requires repair and reconstruction due to cancer resection, trauma, stenosis, or developmental disruptions. Bioengineering has provided some scaffolding materials and initial attempts at tissue engineering, especially of the trachea, have been made. The critical issues of providing protection, maintaining a patent airway, and controlling swallowing and phonation, require that the regenerated laryngotracheal cartilages must have mechanical and material properties that closely mimic native tissue. These properties are determined by the cellular and proteomic characteristics of these tissues. However, little is known of these properties for these specific cartilages. This review considers what is known and what issues need to be addressed.